Diagnosis and treatment of teeth with chronic apical periodontitis with fistula (Эндодонтия Today)
Chronic apical periodontitis permanent tooth can be accompanied by formation of a fistula. A similar clinical case described in the article. Important emphasis on the use of x-ray diagnostics at all stages of treatment, including long-term periods. Quality endodontic exposure end with the sealing of the root canal. Followed by aesthetic restoration of the tooth with the use of modern photocurable composites. Control of sealing is carried out after 3, 6, 12 months.